(untitled) (Research, Society and Development, 2025)
Primary pancreatic lymphoma (PPL) is a rare condition characterized by the presence of a lymphoproliferative neoplasm with primary pancreatic involvement, accounting for approximately 1% of all extranodal lymphomas. This tumor represents 1 to 2% of malignant pancreatic neoplasms, with pancreatic adenocarcinoma being the most common histological type. Its diagnosis is complex due to the nonspecific nature of symptoms and the difficulty in differentiating it from pancreatic adenocarcinoma based solely on imaging studies, which delays definitive diagnosis and the initiation of appropriate treatment. This article aims to report a clinical case of primary pancreatic lymphoma of the diffuse large B-cell lymphoma (DLBCL) subtype, describing its diagnostic process and therapeutic approach. It is a descriptive observational study based on research and electronic medical record review, submitted to the Research Ethics Committee for Human Subjects and approved under the Certificate of Presentation for Ethical Consideration (CAAE) No. 82862724.5.0000.5359.